Optical coherence tomography assessment of axonal and neuronal damage of the retina in patients with familial and sporadic multiple sclerosis - Grudziecka Pyrek, Monika; Selmaj, Krzysztof (Frontiers in Neurology, 2022)
Objective To assess axonal and neuronal damage of the retina in patients with familial (fMS) and sporadic multiple sclerosis (sMS). Methods 87 relapsing-remitting MS patients (45 patients with sMS, 42 patients with fMS) and 30 healthy controls were included in the study. Optical coherence tomography (OCT) was performed with the spectral domain optical coherence tomography (SD-OCT, Heidelberg Engineering, Germany). The peripapillary retinal nerve fiber layer (pRNFL) thickness, ganglion cell-inner plexiform layer (GCIPL) thickness, total macular volume (TMV) and the inner nuclear layer (INL) thickness were measured. Results A significant reduction of the pRNFL thickness was detected in sMS and fMS compared to the control group (86.29 (+/- 16.13) μm in sMS, 84.78 (+/- 12.92) μm in fMS, 98.93 (+/- 6.71) μm in control group; p < 0.001). There was no significant difference in the pRNFL thickness between sMS and fMS (p = 0.5239). The GCIPL thickness was significantly decreased in sMS and fMS compared to the control group [66.0581 (+/- 11.2674) μm in sMS, 63.8386 (+/-10.004) μm in fMS, 76.5074 (+/- 5.0004) μm in control group; p < 0.001]. A significant reduction of the TMV was shown in sMS and fMS compared to the control group [8.4541(+/- 0.4727) mm3 in sMS, 8.3612 (+/- 0.4448) mm3 in fMS, 8.8387 (+/- 0.314) mm3 in control group; p < 0.0011]. No difference in the GCIPL thickness and TMV between sMS and fMS was found (p = 0.3689 and p = 0.3758, respectively). The INL thickness in sMS and fMS did not differ compared to the control group [34.2323 (+/- 2.7006) μm in sMS, 34.5159 (+/- 2.9780) μm in fMS, 33.6148 (+/- 2.0811) μm in control group; p = 0.5971 and p = 0.1870, respectively] and between the two forms (p = 0.4894). Conclusion We confirmed the presence of axonal and neuronal damage of the retina in sMS and fMS. Both forms of MS did not differ significantly from each other with respect to RFNL, GCIPL, MV and INL. ON induced significant reduction of the pRNFL, GCIPL and MV in both groups of pwMS.